Identifying Somatic Lymph Nodes for VLNT Using Technetium-99m Sulfur Colloid - Vasudevan, Srikanth; N. Yelambalase, Anantheswar; Basur Chandrappa, Ashok; Shetty, Mayur R.; RV, Parameswaran; Marwah, Annika; Shetty, Pooja Aditya; Bharathkar, Serena K.; Yande, Aashita R.; Tewari, Chinmay; Pai, Ria; Sharma, Milind; Sara, Nitisha (Indian Journal of Plastic Surgery, 2025)
Vascularized lymph node transplant (VLNT) is one of the treatment options for chronic lymphedema following both breast cancer-related lymphoedema and lower extremity lymphoedema. VLNT is a safe and effective treatment for lymphedema with significant benefits fully manifesting at 2 years postoperatively. This involves the microvascular transfer of lymph nodes to the affected limb. The transferred lymph nodes then act as a sump to drain the excessive lymphatic fluid in the interstitial space. One of the challenges in VLNT is to include an adequate number of lymph nodes in the flap, which requires some way of identifying them before harvesting. In order to transfer lymph nodes along with their vascularity, we have relied on anatomic studies. However, using Technetium-99m sulfur colloid as used in sentinel lymph node harvest, we can identify lymph nodes in the transferred tissue, giving greater reliability to the procedure. It involves identifying the lymph node area before incision, guiding surgerons during harvest of the lymph nodes along with the vascularity, confirming the presence of lymph nodes after harvest, and confirming the presence after microvascular transfer to the affected site. It can be used along with methylene blue dye and indocyanine green (ICG) to confirm the presence of lymph nodes. In our pilot study of eight cases, we have found the presence of lymph nodes in all the transferred tissue. This is in comparison to certain studies on sentinel lymph node studies that indicate that the use of radiotracer and ICG is comparable in localizing lymph nodes.
Keywords: Technetium-99m; vascularized lymph node; lymphoedema; localizing lymph nodes